cONTRIbUTION à l’éTUde deS caRacTèReS PhéNOTyPIQUeS et du potentiel de reproduction de la poule locale : Cas de la région de TIARET - BOUGHEDDOU, Aicha (My University, 2016)
In order to contribute to the study of the determination of phenotypic traits and breeding populations of Algerian local chickens, field investigations are conducted in the wilaya of Tiaret. The hens that are part of the survey are raised in poor environmental conditions and therefore their productivity was low. Phenotypic characterization of the 161 local fowl selected (32 males and 128 females) has revealed a wide phenotypic diversity. The treated body measurements (body weight) confirmed a sexual dimorphism already known for this poultry species with significantly higher body weight values in male (1658g) than females (1543g) Three hundred (300) eggs were used in this study and in which different measures are carried out (weight, length and width). Strong correlations are recorded between the egg weight, its length and width (r = 0.39, r = 0.72, r = 0.30). Moreover, the correlation coefficient between the variables chickens' body weight and egg weight is insignificant and therefore shows no relationship in these two measured parameters. Similarly, the correlation coefficient (r = 0.61) between the egg weight and the chick weight showed no relationship between those two measured variables. There is a high rate of embryo mortality reaching about 59%. From the recorded results, it might be possible to improve relatively breeding conditions (nutrition, sanitation, housing etc ..) in this category of animals to better know the true genetic potential of the poultry population.